Causality between oil prices and exchange rates: a quantile-on-quantile analysis - Seraj, Mehdi; Mar'I, Muhammad; Abdulkareem, Alhassan; Turuc, Fatma (Incisive Media, 2021)
This study examines the causal link between the crude oil price and the exchange rate in five major oil-exporting countries (Saudi Arabia, Russia, Canada, the United Arab Emirates and the United States) that have recently adopted different exchange rate policies. Using a nonlinear causality approach, quantile-on-quantile, with monthly data from April 1996 to January 2020, we find causal relationships between crude oil prices and exchange rates across quantiles in all of the countries studied. A plausible explanation for such findings is that these countries are oil exporters who depend largely on the proceeds of the oil trade. Any shocks in the oil market that affect oil production and price translate to exchange rate fluctuations in these countries. Meanwhile, the effect of the oil price on the exchange rate is diverse and heterogeneous depending on the country's level of crude oil production and consumption, its exchange rate policies and the strength of its economy.
Keywords: oil price; exchange rate; oil-exporting countries; quantile-on-quantile approach